Pengaruh Penerapan Pembelajaran Diferensiasi terhadap Keterampilan Siswa Menulis Paragraf di Kelas VII SMPNegeri 1 Parbuluan - Sitorus , Pontas J.; Siregar , Ance S.N.; Siagian, Beslina Afriani (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Penelitian ini bertujuan Untuk Mengetahui “Pengaruh Penerapan Pembelajaran Diferensiasi Terhadap Keterampilan Siswa Menulis Paragraf di Kelas VII SMP NEGERI 1 PARBULUAN”. Jenis Penelitian ini adalah Penelitian Kuantitatif Eksperimen dengan desain penelitian One grup Pretest dan Posttest design.Populasi dalam penelitian ini adalah seluruh siswa kelas VII dengan jumlah siswa 180 orang dan yang menjadi sampel ini adalah kelas VII-4 sebanyak 30 siswa dan kelas VII-5 sebanyak 30 siswa yang di tentukan dengan Teknik Cluster Sampling . Teknik analisis data yang digunakan adalah uji Normalitas, uji Homogenitas dan Uji Hipotesis. Setelah dilakukan penlitian pada kelas kontrol pretest dan posttest, di peroleh nilai rata-rata pretest yaitu 60 dengan simpangan baku -1,27 dan nilai rata-rata pada posstest yaitu 77,26 dan simpangan baku -3,27 dari hasil pengujian hipotetis dalam penelitian ini dilakukan uji “t” tabel pada taraf signifikan 5% dengan df = N-2. df yaitu 30 maka 28. Dari df 28 diproses taraf signifikan 5% = 1,701. Berdasarkan perhitungan yang telah dilakukan maka, dapat diketahui bahwa thitung> ttabel yaitu 6,76 > 1,701. Dengan demikian hipotesis nihil (HO) di tolak dan hipotesis di terima sehingga dinyatakan bahwa penerapan pembelajaran diferensiasi berpengaruh terhadap kemampuan menulis. Kata Kunci: Pembelajaran Diferensiasi, Menulis Paragraf Deskripsi, Keterampilan Menulis. This study aims to determine "The Effect of Applying Differentiation Learning on Students' Paragraph Writing Skills in Class VII SMP NEGERI 1 PARBULUAN". This type of research is a Quantitative Experimental Research with a One-group Pretest and Posttest research design. The population in this study were all students of class VII with a total of 180 students and the samples were class VII-4 as many as 30 students and class VII-5 as much as 30 students determined by the Cluster Sampling Technique. The data analysis technique used is the Normality test, Homogeneity test and Hypothesis Test. After conducting research on the pretest and posttest control classes, the average pretest score was 60 with a standard deviation of -1.27 and the average value in the posttest was 77.26 and a standard deviation of -3.27 from the results of hypothetical testing in this study. In this case, the table "t" test was carried out at a significant level of 5% with df = N-2. df is 30 then 28. From df 28 processed at a significant level of 5% = 1.701. Based on the calculations that have been done, it can be seen that tcount> ttable is 6.76 > 1.701. Thus the null hypothesis (HO) is rejected and the hypothesis is accepted so that it is stated that the application of differentiation learning affects writing ability. This study aims to determine "The Effect of Applying Differentiation Learning on Students' Paragraph Writing Skills in Class VII SMP NEGERI 1 PARBULUAN". This type of research is a Quantitative Experimental Research with a One-group Pretest and Posttest research design. The population in this study were all students of class VII with a total of 180 students and the samples were class VII-4 as many as 30 students and class VII-5 as much as 30 students determined by the Cluster Sampling Technique. The data analysis technique used is the Normality test, Homogeneity test and Hypothesis Test. After conducting research on the pretest and posttest control classes, the average pretest score was 60 with a standard deviation of -1.27 and the average value in the posttest was 77.26 and a standard deviation of -3.27 from the results of hypothetical testing in this study. In this case, the table "t" test was carried out at a significant level of 5% with df = N-2. df is 30 then 28. From df 28 processed at a significant level of 5% = 1.701. Based on the calculations that have been done, it can be seen that tcount> ttable is 6.76 > 1.701. Thus the null hypothesis (HO) is rejected and the hypothesis is accepted so that it is stated that the application of differentiation learning affects writing ability. Keywords: Differentiation Learning, Writing Descriptive Paragraphs, Writing Skills.